1991
DOI: 10.1161/01.str.22.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Activation of coagulation in acute cardioembolic stroke.

Abstract: The hematologic disorders in patients with acute cardioembolic stroke are not fully understood, and no reliable measures are available to identify patients at high risk for recurrent embolism. We analyzed coagulation and fibrinolytic functions in 22 patients with cardiogenic cerebral embolism ^24 hours after onset and in 25 age-matched controls. The levels of antithrombin HI, protein C, and a^-plasmin inhibitor were significantly lower in the patients than in the controls (/?<0.001, 0.02, and 0.05, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
59
0
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 23 publications
7
59
0
1
Order By: Relevance
“…However, none of the patients in this study fulfilled the diagnostic criteria for DIC as defined by the Japanese Ministry of Health and Welfare, and none of them had any non-cerebral vascular lesions ( 16). Blood coagulation system is activated most prominently in cardioembolic stroke, and subsequently in atherothrombotic cerebral infarction (17)(18)(19). However, in lacunar cerebral infarction, these hemostatic markers are not prominently altered (20)(21)(22).…”
Section: Discussionmentioning
confidence: 78%
“…However, none of the patients in this study fulfilled the diagnostic criteria for DIC as defined by the Japanese Ministry of Health and Welfare, and none of them had any non-cerebral vascular lesions ( 16). Blood coagulation system is activated most prominently in cardioembolic stroke, and subsequently in atherothrombotic cerebral infarction (17)(18)(19). However, in lacunar cerebral infarction, these hemostatic markers are not prominently altered (20)(21)(22).…”
Section: Discussionmentioning
confidence: 78%
“…Top, patient with CBE;Bottom, control subject; Right, maximumLAAarea; Left, minimumLAAarea (transverse plane by transesophageal echocardiograms). It has been clearly shown that left atrial dysfunction due to atrial stunning can be recovered for dozens of minutes after the cessation of PAF, whereas, prolongation of the atrial stunning has been suggested to play a critical role in the thrombus formation in LAA by experimental studies (39)(40)(41)(42) Previous clinical reports demonstrate that the nature of altered coagulation and fibrinolysis are different in various subtypes of ischemic stroke (45). Especially, plasma levels of D-dimer and thrombin-antithrombin III complex are significantly higher in cases with cardioembolic stroke, compared with atherothrombotic or lacunar stroke (46).…”
Section: Resultsmentioning
confidence: 99%
“…Especially, plasma levels of D-dimer and thrombin-antithrombin III complex are significantly higher in cases with cardioembolic stroke, compared with atherothrombotic or lacunar stroke (46). Therefore, screening of the prethrombotic state using these hemostatic markers is useful for the assessment and identification of stroke subtype (45,46). On the other hand, it has been reported that there are no significant differences in fibrinocoagulation activity (including D-dimer) between patients with PAF (including paroxysmal periods) and normal sinus controls (47,48).…”
Section: Resultsmentioning
confidence: 99%
“…27 Thus, plasma concentrations of TAT and D-dimer are useful indicators of patients who are prone to recurrent embolization. 28,29 In the present study, to prove a direct relationship between serum FM level and LAA thrombus occurrence, we performed a multivariate logistic regression analysis of data from more than 200 patients with cerebral infarction, which clearly showed that serum FM level was an independent predictor for LAA thrombus, as compared with TAT, PAI-1, PIC, Ddimer, FDP, and the NIHSS score, which reflect the severity of cerebral infarction.…”
Section: Discussionmentioning
confidence: 79%